Model Artificial Intelligent in E-Learning using Fuzzy Logic (Case Study Sasmoko.Com) - Harna Yossy, Emny; ., Sasmoko; Listriana Kusumastuti, Dwi; Ghadati Rabiha, Sucianna; Indrianti, Yasinta (International Journal of Engineering and Technology, 2018)
The advancement of information technology has been maximally utilized in the world of education, especially in the learning process. One form is e-learning. In its development, e-learning has several problems when faced with the background and needs of students who take part in learning. These differences affect the effectiveness of learning because not all students have the same learning style. To overcome these problems, researchers tried to use fuzzy logic methods. Fuzzy logic is chosen to answer the uncertainty that occurs in learning subjective student characters. Therefore, the study was conducted on one e-learning website called sasmoko.com. The e-learning website is a research method course where students from various backgrounds and needs are used. In this study a model was proposed in assessing student characters on the sasmoko.com website.Â Â